1998
DOI: 10.1111/j.2042-7158.1998.tb03366.x
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 4-Methylbenzoylglycine in Rat Isolated Perfused Kidney and Effects of Hippurates on Renal Mitochondrial Metabolism

Abstract: Hippurates tend to accumulate within proximal tubule cells during renal secretion. High intracellular concentrations can alter proximal tubular function or lead to tubular toxicity. In this study we examined the renal disposition of the hippurate 4-methylbenzoylglycine, a compound known for its high renal intrinsic clearance in-vivo. The effect of intracellular accumulation on mitochondrial respiration was also measured in-vitro and compared with that of the 2-methyl and 4-amino analogues. Experiments were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since MRP4 and BCRP are located at the apical membrane of proximal tubule cells, transport activity depends on the intracellular levels of substrates rather than substrate concentrations in the blood. Previously, Masereeuw et al demonstrated that methyl hippuric acids accumulate during secretory transport in the isolated perfused rat kidney [20], [21]. Furthermore, they showed that 2-methyl hippuric acid levels were 175-times higher in kidney tissue compared to the perfusate and 4-methyl hippuric acid concentrations were even 600-times higher.…”
Section: Discussionmentioning
confidence: 98%
“…Since MRP4 and BCRP are located at the apical membrane of proximal tubule cells, transport activity depends on the intracellular levels of substrates rather than substrate concentrations in the blood. Previously, Masereeuw et al demonstrated that methyl hippuric acids accumulate during secretory transport in the isolated perfused rat kidney [20], [21]. Furthermore, they showed that 2-methyl hippuric acid levels were 175-times higher in kidney tissue compared to the perfusate and 4-methyl hippuric acid concentrations were even 600-times higher.…”
Section: Discussionmentioning
confidence: 98%